2011
DOI: 10.1111/j.1744-6198.2011.00221.x
|View full text |Cite
|
Sign up to set email alerts
|

Making Healthy Connections: Introducing Nursing as a Career Choice to Middle School Students

Abstract: The current economic climate has resulted in many experienced nurses returning to the workforce. Despite this, the nursing shortage is looming in our future and the recruitment of a diverse nursing workforce reflective of the population remains a high priority. The Merrimack Valley in northeastern Massachusetts has two large cities, Lawrence and Lowell, in which the Hispanic and the Southeast Asian populations are disproportionately higher than state and national levels. Through the University of Massachusetts… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 6 publications
1
7
0
Order By: Relevance
“…The finding equally shows that all (100%) respondents have made their career choice. This finding is in line with Knight et al (2011) which indicated that students often begin investigating career choices and discussing their future plans in middle school. Gavin (2008) also lends support to this finding as his study showed that pupils make career choice about the age of 14years.…”
Section: Discussionsupporting
confidence: 78%
See 3 more Smart Citations
“…The finding equally shows that all (100%) respondents have made their career choice. This finding is in line with Knight et al (2011) which indicated that students often begin investigating career choices and discussing their future plans in middle school. Gavin (2008) also lends support to this finding as his study showed that pupils make career choice about the age of 14years.…”
Section: Discussionsupporting
confidence: 78%
“…This finding equally shows that choice of careers is tentative thus a lot might still embrace nursing before finally leaving the school. Knight et al (2011), found in their study that the choice of career is often based on stereotyping instead of awareness of the opportunities. Knight et al (2011), further discovered that some students, following an after-school workshop, had an increased interest in nursing.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In an integrative review for the years 1989–2006, Matutina, found that programs which exposed middle school students to nursing cultivated statistically significant increases in the desire to become or consider becoming a nurse. Since that review, for the years 2007–2016, seven programs have documented recent success with students becoming more aware of the nurses role and inclination to consider nursing as a health career choice …”
Section: Middle School and High School Interventions Increase Awarenementioning
confidence: 99%